The effect of all-trans retinoic acid on cell proliferation and migration during wound healing: an in vitro study - Olateju, Oladiran Ibukunolu (My University, 2011)
Wound healing in skin is a complex process involving inflammatory responses, cell proliferation and migration, and extracellular matrix deposition. While, all-trans retinoic acid (ATRA) is believed to promote wound healing in skin, there are contradictory reports on its effect in both in vivo and in vitro studies. This study aimed at investigating the effects of ATRA at a concentration of 1μM (in DMSO) on cell migration and proliferation in ‘wound’ closure. A HaCaT and a HDF cell line as well as a co-culture of both cell lines were utilized. The cultures were maintained in DMEM supplemented with 5% fetal bovine serum incubated at 37ºC in a 5% CO2 in air humidified incubator. Scratch ‘wounding’ of the HaCaT culture and the co-culture were carried out prior to treatment with ATRA or its controls [DMSO (vehicle control) or DMEM (untreated control)]. ATRA did not have a significant effect on cell proliferation in either the HaCaT or HDF cultures or in the co-cultures. DMSO inhibited proliferation in the HDF cultures and in the co-cultures, while there was no effect on the HaCaT cultures. In addition, ATRA had no significant effect on ‘cell migration’ during ‘wound’ closure in both the HaCaT culture and the co-culture. However, DMSO appeared to be inhibitory to migration of cells in both cultures as there was a significant decrease in migration in cultures grown in DMSO when compared to ATRA treatment. The failure of ATRA to promote cell migration and proliferation during ‘wound’ closure in the HaCaT culture and the co-culture would seem to suggest that the activity of ATRA was compromised by DMSO.
Keywords: Wound Healing